Pengembangan Identitas Spesifik Berbasis Marka SSR pada 29 Varietas Kedelai Lokal Indonesia - Lestari, Puji; Risliawati, Andari; Utami, Dwinita Wikan; Hidayatun, Nurul; Santoso, Tri Joko; Chaerani, Chaerani (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTSoybean is an important legume crop in Indonesia and local varieties from different regions are diversed. Accurate identification of local varieties is needed to determine the genetic identity in order to protect them to indicate the geographical origin and registration purpose. This study aimed to analyze DNA fingerprints of local varieties of soybean in Indonesia to develop a specific identity using SSR markers along with the marker set. A total of 29 local varieties/accessions was analyzed using 9 selected SSR markers with semi automated genetic analyzer on the basis of capillary electrophoresis. Total markers successfully detected 50 alleles in all varieties, with the average polymorphism information content (PIC) of each locus (0.579) and the genetic diversity index (0.629) were quite high as a reflection of diversity of the local varieties. Based on the analysis of the genetic diversity index, PIC, rare alleles, dominant allele frequency, analysis of genetic distance, 6 SSRs (Satt009, Satt038, Satt177, Satt242, Satt308 and Satt114) were selected as a set of markers for variety identification. Although three varieties can not be distinguished because of their close genetic relationship, but the digital coding indicates that local varieties of soybeans have possessed specific identities (ID) representing variation of SSR alleles. The selected SSR loci with additional identifier can be used to develop ID of Indonesian local soybean in the germplasm collection. Overall, the marker set is a powerful tool to complement morphological markers for the protection of local soybean varieties that contribute in accelerating local varieties improvement in the future agriculture.Keywords: specific identity, SSR, Indonesian local soybean variety, DNA fingerprint.